Application of convolutional neural networks to building segmentation in aerial images - Olaleye, Kayode Kolawole; Stellenbosch University. Faculty of Science. Dept. of Mathematical Sciences. Division Applied Mathematics. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.